Peter Talloen. Cult in Pisidia. Religious practice in southwestern Asia Minor from Alexander the Great to the rise of Christianity. - D’Andria, Francesco (Journal of Greek Archaeology, 2018)
P. Talloen’s research into cults and religious practices in Pisidia is the subject of the 10th volume in the series entitled ‘Studies in Eastern Mediterranean Archaeology’ edited by Marc Waelkens, which contains the copious results of the investigations conducted as part of the Sagalassos Archaeological Research Project.